2023
DOI: 10.1108/gkmc-06-2022-0150
|View full text |Cite
|
Sign up to set email alerts
|

Digital data sets management in university libraries: challenges and opportunities

Abstract: Purpose The study aims to identify the prospects and challenges associated with current practices regarding digital data sets management in university libraries in Pakistan. Design/methodology/approach A cross-sectional survey approach was used to collect the data from library and information science (LIS) professionals working in public sector university libraries in Pakistan. A four-part questionnaire was used to collect the data from the respondents. The collected data from 371 participants were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Therefore, success will be achieved if various stakeholders perform their roles per policies and strategies with various influencing factors in perspective. This study is in line with Shah et al (2020), which revealed that “data management, data curation, data mining, data science, data-savvy, and big data purpose is to identify relationships and causal associations, classify and predict events, identify patterns and anomalies, and infer probabilities, interest, and sentiment.”…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 75%
See 1 more Smart Citation
“…Therefore, success will be achieved if various stakeholders perform their roles per policies and strategies with various influencing factors in perspective. This study is in line with Shah et al (2020), which revealed that “data management, data curation, data mining, data science, data-savvy, and big data purpose is to identify relationships and causal associations, classify and predict events, identify patterns and anomalies, and infer probabilities, interest, and sentiment.”…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 75%
“…Any value higher than this shows some levels of predictive accuracy. In Hair et al (2011, 2013) and Henseler et al (2009), R 2 values of .75 are substantial, .50 is moderate, and .25 is weak predictive abilities of the variable. Chin (1998) also articulates the values of 0.67, 0.33 and 0.19 as substantial, moderate and weak, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…While many unknowns persist, making it challenging to quantify the rate of data management per customer, partial digitization has nonetheless led to improvements in database availability, data retrieval, and analysis. The introduction of new technology necessitated training for microfinancing personnel, aligning with findings in studies on e-resource readiness, and emphasizing the need for training in computer applications and data management (Abdulkareem, 2021;Shah et al, 2023). A study on the determinants of employee digital transformation readiness and job performance revealed that employees' attitude, self-efficacy, and characteristics affected their readiness for digital transformation (Thu et al, 2023).…”
Section: Customer Data Managementmentioning
confidence: 86%
“…These methodologies could offer FUPRE valuable insights into handling similar challenges, especially those related to obsolete media formats and the sheer volume of digital files. Moreover, the study on digital data sets management in Pakistani university libraries by Shah et al (2023) presents a broader perspective on the opportunities and challenges inherent in digital data management, including the critical need for leadership support and comprehensive data management planning. This aspect resonates with the strategic requirements at FUPRE, where enhancing digital records management practices necessitates addressing infrastructural and policyrelated challenges while focusing on meeting the diverse needs of data users.…”
Section: Discussionmentioning
confidence: 99%